Second record of Lasiurus ebenus (Chiroptera, Vespertilionidae), with comments on its taxonomic status - Cláudio, Vinícius C.; Barbosa, Gedimar P.; Novaes, Roberto Leonan M.; Rassy, Fabrício B.; Rocha, Vlamir J.; Moratelli, Ricardo (Zootaxa, 2018)
Lasiurus ebenus was known only from the holotype, which was collected in 1991, in an Atlantic Forest remnant of Ilha do Cardoso State Park, southeastern Brazil. The species was described based on qualitative and quantitative morphological features. Since its original description, based on a single individual, the taxonomic status of Lasiurus ebenus has been questioned. Here we report a second record for the species that comes from Carlos Botelho State Park, São Paulo, ca. 100 km north from the type locality. This new record allowed us to confirm the validity of the species, by presenting additional data that fits in the distinction from sympatric congeners proposed on the original description of L. ebenus.